Question-107124 Tinku Tara June 4, 2023 None 0 Comments FacebookTweetPin Question Number 107124 by Khalmohmmad last updated on 08/Aug/20 Answered by mathmax by abdo last updated on 08/Aug/20 letf(x)=3πx−1πxwehave3πx=eπxln(3)=1+πxln(3)+o(x2)⇒eπxln3−1πx=ln(3)+o(x)⇒limx→0f(x)=ln(3) Answered by JDamian last updated on 08/Aug/20 3πx=1+πln31!x+(πln3)22!x2+⋅⋅⋅limx→0(3πx−1πx)=limx→0(ln3+(πln3)22!πx+⋅⋅⋅)==ln3 Terms of Service Privacy Policy Contact: info@tinkutara.com FacebookTweetPin Post navigation Previous Previous post: Question-172662Next Next post: x-3-x-6-x-3-2-1-3-dx- Leave a Reply Cancel replyYour email address will not be published. Required fields are marked *Comment * Name * Save my name, email, and website in this browser for the next time I comment.